Effect of extraction technique on chemical compositions and antioxidant activities of freeze-dried green pepper - Zhang, Chaohua; Gu, Fenglin; Hu, Weicheng; Wu, Guiping; Chen, Weijun; Dong, Conghui; Niu, Zhiqiang (Frontiers in Nutrition, 2022)
In this study, the yield, content of piperine, and antioxidant activity of pepper oleoresin obtained with the methods of maceration, ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), and ultrasound-MAE (UMAE) were analyzed, and the microstructure of pepper residue was observed. For the yield and piperine content, the UMAE method had the best extraction capacity among the four methods. While, the oleoresin obtained with maceration had the highest total phenolic content, and the antioxidant activity of the oleoresin obtained by maceration was higher than that of the extracts acquired by UAE, MAE, and UMAE, and a high positive correlation was observed between the antioxidant activity and total phenolic content of the oleoresin obtained by these extraction methods. The ideal parameters for UMAE were an 80-mesh particle size and a 1 g/10 mL solid–liquid ratio. Then, using first- and second-order models, the kinetic parameters and models of the UMAE extraction process were compared. The second-order kinetic equation with the lowest root mean square deviation and highest adjusted correlation coefficient proved to be more suitable for describing the extraction kinetics of pepper oleoresin. This study showed that UMAE is a fast, efficient, and cost-effective technique for the extraction of green pepper oleoresin.